The factors influencing students’ decision in choosing higher education / Nur Hidayah Rosli and Nurul Fazlin Hanim Hassan - Rosli, Nur Hidayah; Hassan, Nurul Fazlin Hanim (2022)
The purpose of this study is to identify and determine the factors influencing students’ decision in choosing higher education and consequently we find out the relationship between its factors which are financial status, employment opportunity and personal factor with students’ decision in choosing higher education institution. The study was carried out between March 2021 until February 2022. This study adopted a nonprobability convenience sampling technique in collecting the questionnaire from the respondents. The result of the study has found two important findings which are majority of the respondents was agreed that due to employment opportunity and personal factor, they took a decision to continue their studies in the higher education institution. On the other hand, financial status is not the main factor that influence students’ decision to select the university or college as the result obtained is not statistically significant. The primary data was obtained by distributing the questionnaire to the 122 respondents from Universiti Teknologi Mara (UiTM) students at random campuses such as UiTM Seremban 3, UiTM Melaka, UiTM Sabah, UiTM Pahang, UiTM Perlis and other UiTM campuses. In addition, a Cronbach's Alpha Reliability test was performed after the data was collected to determine the reliability of each variable. Pearson Correlation Coefficient was used to identify the relationship between independent variables and dependent variable obtained in this study.